COMPANY SIZE AS A MODERATING VARIABLE ON PROFITABILITY AND CORPORATE SOCIAL RESPONSIBILITY ON TAX AGGRESSIVENESS - Catlina Zanita Lailiyah, Catlina; Amelia Massela, Amelia Massela; Yulianto, Agung (Cirebon International Conference on Education and Economics Proceeding, 2024)
Tax aggressiveness is a tactic used by businesses to lower their profits in order to pay less income tax to the government. Tax avoidance practices can be said to be tax aggressiveness if the company tries to aggressively reduce the tax burden. Tax aggressiveness is still a problem in the business world in Indonesia which results in the government losing potential tax revenue. Using agency theory, this study aims to provide empirical evidence regarding the relationship between profitability and corporate social responsibility on tax aggressiveness. The results showed a positive effect on profitability and a negative effect of corporate social responsibility on tax aggressiveness. Company size has a positive moderating effect on the link between tax aggressiveness and profitability, while the relationship between tax aggressiveness and corporate social responsibility is adversely moderated. As a result, the government must improve oversight and enforcement of aggressive tax evasion strategies, as well as enact additional tax rules to combat tax aggressiveness.